(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Program budowy społeczeństwa socjalistycznego połączony z rywalizacją pomiędzy światowymi układami stawia na pierwszy plan problem organizacyjnej efektywności i wydolności aparatu administracyjnego państwa komunistycznego. Autor artykułu przedstawia założenia ogólne metod działania administracji, gdzie szczególnie zwraca uwagę na metodę prewencji administracyjnej oraz działalności pośredniej. Ponadto charakteryzuje cywilistyczne metody działania administracji oraz opisuje prawne i pozaprawne regulatory metod działania administracji. The programme for the construction of a socialist society, combined with the rivalry between global alignments, brings to the fore the problem of the organisational efficiency and capacity of the administrative apparatus of a communist state. The author of the article presents the general assumptions of the methods of administrative action, where he particularly draws attention to the method of administrative prevention and indirect activity. In addition, he characterises civilian methods of administration and describes the legal and non-legal regulators of administrative method